The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ppap.200931601
|View full text |Cite
|
Sign up to set email alerts
|

High Temporal Resolution Ion Energy Distribution Functions in HIPIMS Discharges

Abstract: A technique for obtaining high time resolution ion energy distribution functions (IEDFs) at the substrate in depositing plasma has been demonstrated, and applied to a high power impulse magnetron sputtering (HIPIMS) discharge. Key to this technique is the electrostatic gating of ions inside the instrument end cap. To demonstrate the performance of this technique, IEDF measurements with a 2 µs time‐resolution have been made with the following HIPIMS operating conditions: a repetition rate of 100 Hz, a pulse wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It has been reported that the time-averaged IEDF can be fitted using the sum of two Maxwellian distributions with different effective ion temperatures originating from the on and off phase of the discharge [127]. Furthermore, the time-resolved measurements show that during the pulse, a Thompson-like high-energy tail distribution of the target material IEDF with energies up to 100 eV has been reported, whereas after the pulse the target material IEDF comprises a main low-energy peak and a high-energy tail [127][128][129]. Several contributions showed that by increasing the working gas pressure, the highenergy tail of the IEDF was reduced and the low-energy peak of the IEDF increased and narrowed as a result of thermalization [124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: Ion Energy Distribution Functions-speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the time-averaged IEDF can be fitted using the sum of two Maxwellian distributions with different effective ion temperatures originating from the on and off phase of the discharge [127]. Furthermore, the time-resolved measurements show that during the pulse, a Thompson-like high-energy tail distribution of the target material IEDF with energies up to 100 eV has been reported, whereas after the pulse the target material IEDF comprises a main low-energy peak and a high-energy tail [127][128][129]. Several contributions showed that by increasing the working gas pressure, the highenergy tail of the IEDF was reduced and the low-energy peak of the IEDF increased and narrowed as a result of thermalization [124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: Ion Energy Distribution Functions-speciesmentioning
confidence: 99%
“…The temporal resolution is limited to 10 µs. Time-resolved measurements were performed in a HIPIMS discharge [125,[127][128][129] where ionization of the sputtered material is up to 80% [156]. Hecimovic et al utilized 20 µs acquisition time to observe the temporal evolution of IEDF of Cr + ions showing dynamic evolution of the ion energies during and after the pulse, figure 19.…”
Section: Time-resolved Measurementsmentioning
confidence: 99%
“…Therefore Ti neutrals with only a few volts of forward kinetic energy, ionized outside the trap can readily reach the substrate (grounded or negatively biased). It is these ions that form the bulk of the deposit in HiPIMS and have been detected by energy-resolved mass spectrometry [29][30][31].…”
Section: The Axial Distribution In V Pmentioning
confidence: 99%
“…IV D. With a mass spectrometer that faces the target Vlček et al observed copper ions that have energies of up to 45 eV, 170 and titanium ions that have energies of up to 50 eV, 171 at 0.6 Pa, and zirconium ions with energies up to 100 eV at 1 Pa. 172 They find Cu þ ions to be up to 80%-95% of the total ion flux to the substrate. 173 Mishra et al 174 also have the mass spectrometer facing the race track region of the target 10 cm from a titanium target. They find Ti þ ions having a high energy tail extending up to 100 eV.…”
Section: B Ion Flux Energy and Compositionmentioning
confidence: 99%